Timeline as a Means of Digital Representation of Theoretical Material* - Zhussupova , R.F.; Kalizhanova , A.N. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2021)
The article depicts the use of Timeline innovative online technology based on the theoretical course "The History of the English language" or "Lingua countrystudy" for students of linguistic specialties. Often in studying theoretical courses modern students have difficulties with tasks related to understanding the cultural and historical context, establishing causal links between historical and linguistic phenomena, remembering social and cultural events. Timeline technology is a description of the sequence of events that occurred in chronological order. This article describes how to use Timeline technology in classrooms, from creating a particular Timeline to testing it in the learning process. In the research given examples and tasks have been analyzed besides the effectiveness of improving theoretical knowledge of the 2nd year students using the platform moodle.enu.kz was detailed. At the end of the course, a survey was conducted in this platform and determined that the Timeline technology contributes to the effective solution of problems, such as the boring presentation of theoretical material, the difficulty in perceiving the authentic text of the old-English period, meets the requirements of distance learning, and moreover is aimed at creative-cognitive and communicative learning of foreign languages.